Local Resource-Based Women Empowerment Model Through Family Development Session (FDS) - Annisa, Yulia (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
This research is motivated by the assumption in the Pungut Hilir Village community that the economic control of the family is the role of men as the head of the family. The task of women, as housewives, is to manage the household and care for children. It raises the opinion that women do not have a role in managing the existing local resources. Through this study, the researcher aims to discuss a model of empowering women based on Local Resources in the Family Development Session (FDS) Group. An Empowerment model for women is implemented to challenge this societal assumption. This empowerment model is not only to improve skills but also to enhance knowledge and change the community’s mindset about the role of women in managing local resources. It also aims to increase the participation of women in Pungut Hilir Village in utilizing local resources. This field study is analyzed using qualitative methods, including data reduction, data presentation, and drawing conclusions. Data collection techniques involve observation, interviews, and documentation. The findings of this study reveal that housewives play a crucial role in economic development through FDS groups to enhance family economic stability. An effective empowerment model for the FDS group in managing local resources is the Local Community Development Model, which aims to develop capabilities and increase awareness to achieve desired goals. The objectives are implemented as follows: 1) improving the knowledge of FDS members through the design thinking model for knowledge dissemination, socialization, and capacity-building training; 2) enhancing the skills of FDS members independently by providing training and mentoring to process local potential into woven products, food, and herbal products; and 3) increasing the participation of FDS members through productive activities such as education, joint ventures, and cooperative savings and loans.